ANALISIS GAYA BELAJAR PESERTA DIDIK SEBAGAI PERSIAPAN PEMBELAJARAN DIFERENSIASI DI KELAS 1 SD SUPRIYADI 02 SEMARANG - Nur Khomsanah; Joko Sulianto; Qoriati Mushafanah (STKIP Subang, 2023)
This study aims to get an overview of the tendency of participants' learning styles as a preparation for differentiated learning in class 1B SD Supriyadi 02 Semarang. The results of this research are intended for initial assessments in overall differentiated learning. This research is a qualitative descriptive research. The method used is a survey with a self-developed learning style questionnaire based on Bobby De Potter's formulation of learning styles. According to Bobby De Potter there are 3 types of learning style tendencies, namely visual, auditory, and kinesthetic. Based on the results of the research, it shows that there are no students who absolutely only rely on one learning style. Learners' learning styles show a combination of the three learning styles. Differentiated learning is intended to facilitate the diverse needs of students. The research was conducted by PPL 1 students of the elementary school teacher education professional program, and the research was conducted on class 1B students because the mapping of students' needs should have started from the beginning when students entered a school.